2019
DOI: 10.1002/anie.201901939
|View full text |Cite
|
Sign up to set email alerts
|

meta‐ and para‐Phenylenediamine‐Fused Porphyrin Dimers: Synthesis and Magnetic Interactions of Their Dication Diradicals

Abstract: meta-and para-Phenylenediamine-fused nickel(II) porphyrin dimers were synthesized by S N Ar reaction of meso,b,b-trichloro nickel(II) porphyrin with meta-and paraphenylenediamines and subsequent Pd-catalyzed intramolecular CÀHa rylation. Their tetrachlorinated dication diradicals are very stable,allowing SQUIDmagnetometry and revealing clear open-shell characters for both meta and para isomers with ferro-and anti-ferromagnetic interactions,r espectively. The nitrogen analogue of Thielesh ydrocarbon usually dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Following the initial syntheses of I and II, a variety of other derivatives, [9] including nitrogen analogues such as III [10] and IV [11] (Scheme 1), were prepared and studied. [12] Ghadwal et al reported the N-heterocyclic carbene (NHC) analogue (V) of Thieles hydrocarbons. [13] Recent theoretical studies by Munz et al and Zeng et al independently pointed to cyclic-(alkyl)(amino)carbene (CAAC) analogues (VI) of Thieles hydrocarbon (Scheme 1) as excellent candidates for optoelectronic applications.…”
mentioning
confidence: 99%
“…Following the initial syntheses of I and II, a variety of other derivatives, [9] including nitrogen analogues such as III [10] and IV [11] (Scheme 1), were prepared and studied. [12] Ghadwal et al reported the N-heterocyclic carbene (NHC) analogue (V) of Thieles hydrocarbons. [13] Recent theoretical studies by Munz et al and Zeng et al independently pointed to cyclic-(alkyl)(amino)carbene (CAAC) analogues (VI) of Thieles hydrocarbon (Scheme 1) as excellent candidates for optoelectronic applications.…”
mentioning
confidence: 99%
“…Synthesis of amine appended A 3 ‐porphyrins with amine nucleophiles through different halogenation strategies. by Osuka et al [ 122–124 ] Ar = 3,5‐di‐ tert ‐butylphenyl.…”
Section: Snar Reactions Of Porphyrinsmentioning
confidence: 99%
“…Treatment of trichloro‐triaylmetalloporphyrin 66 , with N,N'‐diarylated m ‐ and p ‐phenylenediamines and NaO t Bu in DMF yielded the bis(porphyrinyl)amines, m ‐ 67 , in 62 % and p ‐ 67 in 16 %. [ 123,124 ] The main difference aside from the use of different types of amines is the trihaloporphyrin precursor. In the case of 65a , b the initial reactions were performed using the 20‐chloro‐2,18‐iodoporphyrin, however when the same reactions were attempted with 66 , this yielded a complex inseparable mixture.…”
Section: Snar Reactions Of Porphyrinsmentioning
confidence: 99%
“…Considering the strong electronic interactions in fused porphyrins arrays, helically fused porphyrin oligomers will be a promising platform for excellent chiroptical materials. With these backgrounds, we have developed helically fused porphyrin oligomers with trimethylenemethane‐ and benzene‐1,3,5‐triamine‐cores ( 4M ) . Unfortunately, these multi‐porphyrin systems can interconvert rapidly between two enantiomers, hampering their optical separation.…”
Section: Figurementioning
confidence: 99%